Comparative analysis between transportation modes for sustainability perspective in one metropolitan region of southern Brazil - Laura Visintainer Lerman; Amália Koefender; Guilherme Brittes Benitez; Mateus José do Rêgo Ferreira Lima; Alejandro Germán Frank (Production)
Abstract Paper aims The objective is to make a comparative analysis between different transportation modes used in the Metropolitan Region of Porto Alegre and to analyze its performance in relation to time, cost and carbon emissions. Originality Investigation of the urban mobility situation on the perspective of sustainability in a Latin American city, including the analysis of Uber pool, implemented in November 2018 in the metropolitan region analyzed. Research method A case study was carried out in the metropolitan area of Porto Alegre, as well as the definition of 4 different routes used as unit of analysis for different types of transportation modes. Main findings Riding bicycle is a very convenient transportation mode in terms of its environmental perspectives and costs. However, the time of locomotion using bicycle is superior in relation to other modes of transportation. Therefore, riding a private car still stands out in the comparisons between different types of transport, since it is a faster mode of transportation. Implications for theory and practice As riding bicycle is a very convenient transportation mode, we highlight the importance of encouraging its use. People can benefit from practicing physical exercise while moving from one place to another and also benefit the environment from lowering carbon emissions.